The Choreography: Unakarn Panji Chom Suan Khwan - Phetruchee, Mananshaya (Journal of Cultural Approach, 2025)
"The Choreography: Unakarn Panji Chom Suan Khwan" aims to create a choreographed Thai court dance performance inspired by King Rama II’s royal writings. The process incorporates several elements, such as literature, personal experiences, observations, recordings, interviews, and internal expert evaluations. Our process involves data analysis, innovative dance creation, qualitative data recording, and external expert review and evaluation. Quantitative data analysis employing statistical measures such as the mean and standard deviation. We employed analytical, descriptive, and narrative methodologies to elucidate the findings of the study. According to the research, King Rama II established the Unakarn. It is distinct from the Kaluh in Pan-Ji mythology. The choreographer created Unakarn’s dance with a feminine aesthetic, emphasizing gender inclusivity by including elements from Thai literature and culture. In "Unakarn Panji Chom Suan Khwan," the duo dance demonstrates Suan Kwan’s beauty through skillful execution, elegance, and meaningful movements. The performance is replete with exuberance, sorrow, and exhilaration. The proposal indicates that traditional designers of royal dance require originality, expertise, choreographic experience, and thorough research. The choreography has three sequential steps: the first step, Phitphan Phueksa Sena Arun, involves appreciating and desiring plants; the second step, the Borron Rit Ron Jap Phirut, involves evaluating power and weaknesses; and the third step, Phak Sapparut Ruen Phirom, involves a pleasurable combat intermission, utilizing three design principles: 1) text; 2) initials; and 3) altered motions. Four experts, with an average inventiveness score of 4.75 and an average appropriateness and satisfaction score of 5.00, deemed the choreographic work highly effective.